As lutas dos trabalhadores por moradia em Foz do Iguaçu, Paraná (1970-1990) - Gaspar, Lucas Eduardo (2017)
Look at a city and realize the importance of social practices of workers Is one of the main efforts of this work. The decade of the 1970s, 1980s and 1990s, Were the scene of transformations in the city of Foz do Iguaçu, in addition to the common transformations, reproduced by the official history (construction of the Itaipu Plant, advancement of trade and tourism), this work proposes an analysis of the period under another perspective. Departing essentially from the trajectories of the working class of the city It was possible to investgate various practices and conflicts, in the course of three decades in relation to housing. Reflecting on how different forms of housing struggles carried out by workers in Foz do Iguaçu, We can approach deeper questions about how these subjects attribute meanings as social practices, as their variable practices and also how this theme allows to glimpse in a more general way The workers' struggle for permanence and for the city itself. The selected spatial cutout has the largest areas of the city - the Porto Meira Region and the São Francisco Region - which are predominantly composed by workers areas and constitute disputes areas during the history of Foz do Iguaçu.